PENGEMBANGAN MEDIA PEMBELAJARAN SWAPMASTER UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KOMPUTASIONAL - Yudhistira Wirayudha Pratama; Muhammad Alfan; Ratna Agustyasari; Kanzul Fikri Fauzi; Moh. Nur Zamzami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Computational thinking skills are skills needed to solve various problems that arise in everyday life. Based on the international study of the Programme for Student (PISA), Indonesian students have low thinking and reasoning skills. Therefore, this study aims to develop a game-based learning media (product) called